Political Sociology - Wood, James (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
In this course in political sociology, we will study three related topics:(1) the distribution of power in the United States;(2) the organization and mobilization of political groups; and(3) an analysis of one political movement, the student movement.